2017
DOI: 10.1245/s10434-017-5837-z
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic Biopsy of Internal Mammary Lymph Nodes During Immediate Breast Reconstruction After Mastectomy for Breast Malignancies

Abstract: Aggressive IMN evaluation and biopsy in a subset of patients during immediate breast reconstruction using a TRAM free flap provided an additional opportunity for accurate breast cancer staging and appropriate adjuvant treatment, while minimizing unnecessary complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…In addition, how the reconstruction method was chosen is another important factor that could not be assessed because of the retrospective nature of the study. However, as several previous important retrospective studies [32,33], we assume discovering novel findings from retrospective cohort study is virtually not impossible. We hope further study with robust research design (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, how the reconstruction method was chosen is another important factor that could not be assessed because of the retrospective nature of the study. However, as several previous important retrospective studies [32,33], we assume discovering novel findings from retrospective cohort study is virtually not impossible. We hope further study with robust research design (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…Lastly, since we used a retrospective design, we could not be certain that some information that might have influenced the outcome was not left out. However, as several previous important retrospective studies 31,32 , we assume discovering novel findings from retrospective cohort study is virtually not impossible. We hope further study with robust research design (e.g.…”
Section: Discussionmentioning
confidence: 96%
“…When using a free flap for immediate autologous reconstruction after mastectomy, the internal mammary artery (IMA) and IMV are the preferred recipient vessels because of their large caliber and high flow rate, which provides a reasonable opportunity to study IMLN metastasis. Recent studies have identified that 3.6-6% of breast cancer patients have positive IMLNs based on biopsy performed during immediate reconstruction after mastectomy [48][49][50]. However, among 2057 patients who underwent free-flap breast reconstruction, Ochoa et al [51] found that only 28 patients (1.3%) had positive IMLNs, and the preoperative breast MRI provided 11% sensitivity for detecting the IMLN.…”
Section: Histopathologically Confirmed Imln Metastasismentioning
confidence: 99%
“…Many studies have investigated the relationships between IMLN metastasis and various clinical, pathological, and immunohistochemical parameters. Among newly diagnosed breast cancer patients, IMLN metastasis is associated with age, tumor location/depth, and the tumor's expression of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor-2 (HER-2) [2,9,40,50,[80][81][82][83][84][85]. For example, Heuts et al [2] reported that the proportions of IMLN metastasis were 32% for < 50-yearold patients, 15% for 51-to 70-year-old patients, and 11% for > 70-year-old patients in their cohort.…”
Section: Predictive and Prognostic Factors Of Imln Metastasismentioning
confidence: 99%